2013
DOI: 10.1080/1461670x.2013.837255
|View full text |Cite
|
Sign up to set email alerts
|

Branding Post-War Sarajevo

Abstract: After the violent wars of the 1990s, Bosnia and Herzegovina is heavily promoting its tourism industry with the capital city of Sarajevo as the prime destination. Sarajevo became a city of death during 1992-1995, and its siege remains etched in local and global memories as a time of bombing, horrific shelling of locals, and brutal destruction of the city's cultural heritage. Today Sarajevo faces many dilemmas, including how to remember the 1990s trauma and how to represent the city to citizens and foreign visit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 33 publications
(48 reference statements)
0
10
0
2
Order By: Relevance
“…The media represent current events to diverse audiences (Abazi & Doja, 2017) and influence popular perceptions of tourist destinations (Volcic et al, 2014). Accordingly, the media has become an important source of information for tourism researchers (Li et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The media represent current events to diverse audiences (Abazi & Doja, 2017) and influence popular perceptions of tourist destinations (Volcic et al, 2014). Accordingly, the media has become an important source of information for tourism researchers (Li et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The third article is "Branding post-war Sarajevo: Journalism, memories, and dark tourism" by Z. Volcic (2014) [40]. This article examines how Sarajevo has sought to preserve its cultural heritage following the war, despite significant damage caused by conflict and neglect.…”
Section: Previous Case Studies From Other Parts Of the Worldmentioning
confidence: 99%
“…Bringing the discussion back to the tourism realm, we must acknowledge that these imaginaries and dynamics of dispossession have also been reinforced by the tourism industry in various post-conflict spaces. Evidence from Sri Lanka (Buultjens et al, 2016), Cambodia (Winter, 2008) Bosnia and Herzegovina (Volcic et al, 2014), Cyprus (Scott, 2012), and Colombia (Ojeda, 2012), demonstrated that tourism can be a source of structural violence, particularly when large operators advanced their interests to the detriment of several local communities. In these contexts, tourism is used as a gateway for the privatisation of common goods, deregulation, displacement, and the commodification of people, places, cultures, and pasts (B€ uscher & Fletcher, 2017;Devine & Ojeda, 2017).…”
Section: Structural Violence In Post-conflict Contexts: a Challenge Fmentioning
confidence: 99%